2016
DOI: 10.1111/gbb.12313
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between aggression, brain monoamines and fur color mutation in the American mink

Abstract: Domestication of wild animals alters the aggression towards humans, brain monoamines and coat pigmentation. Our aim is the interplay between aggression, brain monoamines and depigmentation. The Hedlund white mutation in the American mink is an extreme case of depigmentation observed in domesticated animals. The aggressive (-2.06 ± 0.03) and tame (+3.5 ± 0.1) populations of wild-type dark brown color (standard) minks were bred during 17 successive generations for aggressive or tame reaction towards humans, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…Results from long-running experiments using captive silver foxes (Vulpes vulpes) demonstrate that sustained breeding selection against aggressive stress reactivity provokes a range of unselected domestication-typical traits ('domestication syndrome') within a given lineage (Trut, 1999;Trut et al, 2009). Similar effects are documented in mink (Kharlamova et al, 2000;Kulikov et al, 2016), in rats (Albert et al, 2008;Singh et al, 2017), in chickens (Agnvall et al, 2017;Jensen, 2006), and in semi-domesticated mice (Geiger, Sánchez-Villagra, & Lindholm, 2018). Rather than repeated random mutation of genes controlling each commonly altered feature across multiple domesticated lineages and taxa, many domesticated traits are proposed to result from shared developmental shifts (Belyaev, 1979;Fallahsharoudi et al, 2015;Osadchuk, 1998;Trut et al, 2009).…”
mentioning
confidence: 80%
“…Results from long-running experiments using captive silver foxes (Vulpes vulpes) demonstrate that sustained breeding selection against aggressive stress reactivity provokes a range of unselected domestication-typical traits ('domestication syndrome') within a given lineage (Trut, 1999;Trut et al, 2009). Similar effects are documented in mink (Kharlamova et al, 2000;Kulikov et al, 2016), in rats (Albert et al, 2008;Singh et al, 2017), in chickens (Agnvall et al, 2017;Jensen, 2006), and in semi-domesticated mice (Geiger, Sánchez-Villagra, & Lindholm, 2018). Rather than repeated random mutation of genes controlling each commonly altered feature across multiple domesticated lineages and taxa, many domesticated traits are proposed to result from shared developmental shifts (Belyaev, 1979;Fallahsharoudi et al, 2015;Osadchuk, 1998;Trut et al, 2009).…”
mentioning
confidence: 80%
“…The formation of fur color in mammals is a complex process influenced by diverse factors, including the environment, management, and the genetic background [2,3]. Briefly, the relative quantity and distribution of melanocyte products, such as eumelanin and pheomelanin, determine the fur color [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In animals, such intraspecies hierarchy is a result of agonistic aggressive behavior defined by ethologists as an innate form of action to protect oneself, shelter, progeny, and territory (Lorenz, 2002). Artificial selection of animals for either aggressiveness (Kulikov et al, 2016) or domestication (Belyaev, 1979) has demonstrated the contribution of genetic factors to the phenotypic manifestation of aggressiveness (Ehrman and Parsons, 1981; Moore, 2013). Finally, a genome-wide search for genetic factors of both fear and aggressive behaviors has been conducted on model animals, e.g., in canines, which were artificially selected for both domestication and agonistic behavior (Zapata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%